PENYIDIKAN TERHADAP TINDAK PIDANA PERAMBAHAN KAWASAN HUTAN CAGAR BIOSFER GIAM SIAK KECIL OLEH KEPOLISIAN RESOR BENGKALIS BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - Marsela, Sharah; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the case of encroachment Forest neighborhood Biosphere Reserve Giam Siak Kecil this, the Investigator is the person doing the investigation consisting of officials that the State Police of the Republic of Indonesia (INP) which is divided into official investigators full and investigation authorities helpers, as well as civil servants particular by special authority of the law. The case of encroachment of forest land biosphere reserve is done by the village Government-owned land sold to people to buy the land with the intention to expand the village.From the research there are three main issues that can be inferred. First, the Crime Investigation Encroachment Against Forest Region Biosphere Reserve Giam Siak Kecil By Police Bengkalis has not done effectively, because there are many cases of forest fires and encroachment of forest areas Cgar Giam Siak Kecil Biosphere in Bengkalis. Second, barriers experienced by Police Bengkalis is terkendalanya with mapping experts, lack of personnel and budget to the investigation. Third, efforts made to deal with cases of encroachment of Forest Areas Biosphere Reserves Giam Siak Kecil by the formation of a special team for the investigation of the case in the field of forestry and their budget from the Government. Advice writer, First, To Police Bengkalis Particularly in the field of Criminal Sat Tipiter in order to realize the environmental crime law enforcement, are expected to always be consistent and always improve deficiencies in its function as law enforcement officers were repressive. So that law enforcement action against the perpetrators of encroachment of forest areas Biosphere Reserve Giam Siak Kecil and burning the land can be treated with the maximum and no more cases of forest fires in Bengkalis, Second, in the implementation of the investigations conducted by the investigator Police Bengkalis with civil servants must cooperated well in order to expedite the completion of the investigation, and the government also should create a budget for an investigation, the Third, the Importance formed a special team for an investigation because more personnel will speed up the investigation process so that performance is more leverage and focused.Keywords: Investigation - Crime - Giam Siak Kecil Biosphere Reserves